Agglomeration of silicon dioxide nanoscale colloids in chemical mechanical polishing wastewater: influence of pH and coagulant concentration - Noor Aina, Mahomad Zuki; Sin, Jing Yao; Jada, Amane; Dashti, Fereidonian; Fatehah, Mohd Omar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Chemical mechanical polishing (CMP) wastewater generated from semiconductor manufacturing industries is known to contain residual organic and inorganic contaminants, i.e. photoresists, acids, including silicon dioxide (SiO2), nanoparticles (NPs) and others. Nanoscale colloids in CMP wastewater have strong inclination to remain in the suspension, leading to high turbidity and chemical oxygen demand (COD). Although various types of pre-treatment have been implemented, these nanoparticles remain diffused in small clusters that pass through the treatment system. Therefore, it is crucial to select suitable pH and coagulant type in the coagulation treatment process.
Keywords: CMP wastewater; chemical wastewater; colloids; pH; ścieki CMP; ścieki chemiczne; koloidy